On sample size estimation of the arithmetic mean of a lognormal distribution with and without type i (1997)
This article presents several formulas to approximate the required sample size to estimate the arithmetic mean of a lognormal distribution with desired accuracy and confidence under and without the presence of type I censoring to the left. We present tables of exact sample sizes which are based on Land's exact confidence interval of the lognormal mean. Monte Cario estimates of coverage probabilities show the appropriateness of these exact proposed sample sizes at 95% confidence level.